INFLUENCE OF UNETHICAL PRACTICES ON THE EFFECTIVE MANAGEMENT OF COLLEGES OF EDUCATION IN DELTA STATE - Ofojebe, W. N. (UNIZIK Journal of Educational Management and Policy, 2018)
This study focused on the influence of unethical practices on the effective management of Colleges of Education in Delta State. It employed the descriptive survey research design. Four research questions guided the study. The proportionate stratified sampling technique was used to draw a sample of 449 academic staff out of a total population of 898 academic staff in three Colleges of Education (COEs) in Delta State. A questionnaire titled: â€œInfluence of Unethical Practices on the Effective Management Questionnaireâ€ (IUEPEMQ), which contained 63 items, designed on a 4 point scale and arranged into 4 clusters, was used as instrument for data collection for this study. The instrument was validated by three experts who are lecturers in the Faculty of Education, Nnamdi Azikiwe University. A reability coefficient of 0.80 was obtained for the instrument. Data were analyzed using mean scores to answer the research questions. The findings revealed among others that there were some prevalent unethical practices that influence the effective management of Colleges of Education in Delta State. Based on the findings, it was recommended among others that the government and education stakeholders such as the regulatory agency for COEs â€“The Nigeria Council for the Colleges of Education(NCCE) and the administrative heads of secondary schools should ensure that the prevalent unethical practices like extortion and forceful sale of textbooks to students, cultism, sexual harassment, plagiarism, irregular attendance to classes by lecturers, among others, are curtailed to the barest minimum in the institutions.